PENGEMBANGAN MEDIA INTERAKTIF BERBASIS WEBSITE PADA MATERI FOTOSINTESIS KELAS IV SDN JAPANAN 2 KABUPATEN JOMBANG - Oktaviana, Widya; Pratiwi, Emy Yunita Rahma; amohd.Amin, Nor Fadila Binti (Prodi Pendidikan Guru Sekolah Dasar, 2024)
The following are the objectives of this research: 1. Creating an interactive learning media process for fourth grade students of SDN Japanan II through the website. Describe the feasibility of interactive online learning media on photosynthesis material for fourth grade students of SDN Japanan II. 3. Describe the usefulness of website-based interactive media on photosynthesis material for fourth grade students of SDN Japanan 2. This research is a type of research and development. There are 5 phases of this research and development and use the ADDIE development model. 4th grade elementary school students became the research subjects in this study. User response questionnaire and validation sheet are the research instruments. The results showed that the material expert validator gave a result of 97%, the media expert validator gave a result of 90%. The response questionnaire from the teacher gave a product trial result of 96.8%, while the response questionnaire from students gave a result of 94.5%. This means that this media is very valid and very practical to be applied to science learning activities for fourth grade students of SDN Japanan 2.cal to be applied to science learning activities for fourth grade students of SDN Japanan 2.